Fluid-mineral dynamics at the Rincón de la Vieja volcano—hydrothermal system (Costa Rica) inferred by the study of major, minor and rare earth elements in the hyperacid crater lake - Pappaterra, Sabrina; Inguaggiato, Claudio; Rouwet, Dmitri; Levresse, Gilles; Peiffer, Loic; Apollaro, Carmine; Mora-Amador, Raúl; Ramírez-Umaña, Carlos; González, Gino; Schiavo, Benedetto; Kretzschmar, Thomas Gunter; Brusca, Lorenzo (Frontiers in Earth Science, 2023)
Volcanic lakes are complex natural systems and their chemical composition is related to a myriad of processes. The chemical composition of major, minor, Rare Earth Elements (REE) and physico-chemical parameters at the hyperacid crater lake of Rincón de la Vieja volcano (Costa Rica) are here investigated during the pre-unrest stage (2013-2014) of the current phreatic eruption cycle. The ∑REE dissolved in the crater lake varies from 2.7 to 3.6 mg kg-1 during the period of observation. LREEN-local rock patterns are depleted in the water lake samples. On the contrary LREEN-local rock enriched patterns are found in the solid precipitated (mainly gypsum/anhydrite) from lake water samples in laboratory at 22°C. The low variability of (La/Pr)N-local rock and (LREE/HREE)N-local rock ratios (0.92-1.07 and 0.66-0.81, respectively) in crater lake waters is consistent with the stability of volcanic activity. No clear changes in the REE chemistry are associated with the phreatic eruption occurred at mid-2013. The ISOSOL plot is here used to investigate the processes responsible for major and minor element variations. The results show that rock dissolution and mineral precipitation/dissolution are the main processes that control the variability of the lake chemical composition over time. In particular, precipitation and dissolution of gypsum and alunite are responsible for the variations of REE in the waters. Despite the low variations of (La/Pr)N-local rock and (LREE/HREE)N-local rock ratios, this study allows to suggest that REE can be used, together with major elements, as practical tracers of water-rock interaction processes and mineral precipitation/dissolution at active hyperacid crater lakes over time, also during periods of quiescence and low volcanic activity.